Justice beliefs and cultural values predict support for COVID-19 vaccination and quarantine behavioral mandates: a multilevel cross-national study. Issue 2 (17th January 2022) - Lucas, Todd; Manning, Mark; Strelan, Peter; Kopetz, Catalina; Agostini, Maximilian; Bélanger, Jocelyn J; Gützkow, Ben; Kreienkamp, Jannis; Leander, N Pontus; ,
Abstract: Understanding how individual beliefs and societal values influence support for measures to prevent SARS-CoV-2 transmission is vital to developing and implementing effective prevention policies. Using both Just World Theory and Cultural Dimensions Theory, the present study considered how individual-level justice beliefs and country-level social values predict support for vaccination and quarantine policy mandates to reduce SARS-CoV-2 transmission. Data from an international survey of adults from 46 countries ( N = 6424) were used to evaluate how individual-level beliefs about justice for self and others, as well as national values—that is, power distance, individualism, masculinity, uncertainty avoidance, long-term orientation, and indulgence—influence support for vaccination and quarantine behavioral mandates. Multilevel modeling revealed that support for vaccination and quarantine mandates were positively associated with individual-level beliefs about justice for self, and negatively associated with country-level uncertainty avoidance. Significant cross-level interactions revealed that beliefs about justice for self were associated more strongly with support for mandatory vaccination in countries high in individualism, whereas beliefs about justice for others were more strongly associated with support for vaccination and quarantine mandates in countries high in long-term orientation. Beliefs about justice and cultural values can independently and also interactively influence support for evidence-based practices to reduce SARS-CoV-2 transmission, such as vaccination and quarantine. Understanding these multilevel influences may inform efforts to develop and implement effective prevention policies in varied national contexts. Abstract : Shared national values and one's own beliefs about justice simultaneously influence support for policies that aim to encourage COVID-19 vaccination and quarantine.